Pengaruh Lingkungan Kerja Terhadap Motivasi Kerja Pegawai pada Kantor Dinas Komunikasi Dan Informatika Kota Pare-Pare - Titik Subaidah; Tenri S.P. Dipoatmodjo; Agung Widhi Kurniawan; Uhud Darmawan Natsir; Rezky Amalia Hamka (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
This research aims to determine whether work environment variables have a positive and significant influence on employee work motivation at the Pare-pare City Communication and Information Office. This research uses a quantitative approach using multiple linear regression analysis methods with the help of SPSS version 27 data processing to prove three hypotheses. The results of this research indicate that there is a positive and significant influence between physical work environment variables on employee work motivation. Meanwhile, the non-physical work environment has a positive and significant influence of non-physical work environment variables on employee work motivation. Simultaneously, the physical work environment and non-physical work environment have a positive and significant effect on employee work motivation at the Pare-Pare City Communications and Information Office. From the research results, it was found that the work environment is closely related to employee work motivation, both in terms of the physical work environment and the non-physical work environment, proving that the better the work environment, the higher the employee work motivation. Both have a positive and significant influence on employee work motivation. The better the work environment, the better the influence on employee work motivation